43.3k views
2 votes
Solve equation for indicated variable:

g= -2 x + 1 , for x

User Andreu
by
4.9k points

2 Answers

3 votes

Answer:

-(g-1)/2=x

Explanation:

g=-2x+1

subtract one from both sides

g-1=-2x

divide both sides by -2

(g-1)/-2=x

User HHHH
by
5.3k points
3 votes

Answer:


\large\boxed{x=(1-g)/(2)}

Explanation:


g=-2x+1\\\\\Downarrow\\\\-2x+1=g\qquad\text{subtract 1 from both sides}\\\\-2x+1-1=g-1\\\\-2x=g-1\qquad\text{divide both sides by (-2)}\\\\(-2x)/(-2)=(g-1)/(-2)\\\\x=(-(1-g))/(-2)\\\\x=(1-g)/(2)

User Nash
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.